IMPLEMENTASI PASAL 76 HURUF I UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Radjak, Karmila Damariani; Manti, Newista (IBLAM LAW REVIEW, 2023)
This research aims to determine the implementation of Article 76 Letter I of Law Number 35 of 2014 concerning Child Protection, and also to determine the factors that cause child exploitation in Gorontalo City. The research method used in this writing is empirical normative legal research with a descriptive approach to provide researched data about people, conditions or other symptoms. Data collection techniques were obtained from observations, interviews, and documentation conducted by researchers. The results of this study indicate that the implementation of Law Number 35 of 2014 has not gone as expected. Meanwhile, the child protection law was created with the aim of ensuring that children's rights are fulfilled, so that they can live, grow and develop, and receive protection from violence and discrimination. Factors influencing the implementation of Law Number 35 of 2014 are the weak implementation of the regulations that have been established and the lack of involvement of relevant agencies in dealing with street children as well as the lack of cooperation between agencies and law enforcement Police Units (Satpol) in collecting beggars in the field. and there is no specific Regional Regulation (Perda) that regulates beggars and homeless people.